The Churchill factor : how one man made history - Johnson, Boris (New York : Riverhead Books, a member of Penguin Group (USA), 2014)
The mayor of London and former Spectator editor challenges popular misconceptions to assess Churchill's enduring influence on the world, discussing the many contradictions of his life and his considerable political and military achievements.
Introduction: A dog called Churchill -- The offer from Hitler -- The non-Churchill universe -- Rogue elephant -- The Randolph factor -- No act too daring or too noble -- The great dictator -- He mobilised the English language -- A proper human heart -- My darling Clementine -- The making of John Bull --'The most advanced politician of the time' -- No glory in slaughter -- The ships that walked -- The 100-horsepower mental engine -- Playing roulette with history -- An icy ruthlessness -- The wooing of America -- The giant of the shrunken island -- The cold war and how he won it -- Churchill the European -- Maker of the modern Middle East -- The meaning of his name today -- The Churchill factor.
Includes bibliographical references (pages 369-375) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid
Keywords: Churchill, Winston, -- 1874-1965.; Churchill, Winston, -- 1874-1965 -- Military leadership; Prime ministers -- Great Britain -- 20th century -- Biography; Politicians -- Great Britain -- 20th century -- Biography; World War, 1939-1945 -- Great Britain; Great Britain -- Politics and government -- 20th century; Biography